PARTISIPASI UMAT HINDU DAN ISLAM DALAM KEGIATAN KEAGAMAAN DI DESA KERAMAS KECAMATAN BLAHBATUH KABUPATEN GIANYAR - I Nyoman Subagia (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2016)
The Republic of Indonesia consists of diverse ethnic groups, races and culture that are subject to the Indonesian Constitution of 1945 and Pancasila as the nation ideology, which generates the freedom of association and religion. Today, however, the Constitution functions as a mere symbol and has not been implemented in the nation life which in turn trigger conflicts happening in Indonesia. Within the conflict itself, there exists positive participation between religious groups deriving from both Islam and Hinduism in the village of Keramas, Blahbatu, Gianyar district. Its realization is visible in the participation of religious activities and even in social life. Driven by this findings, there are two issues to be discussed in this article as follows: 1) to understand the participation of both the Hindus and Muslims in religious activities in the village, and 2) to investigate the efforts of the Hindus and Muslims in enhancing religious activities in the village. Furthermore, it is hoped that the research findings are useful in uncovering the horizon of universal brotherhood and mutual respect in regard to participation. This research is also applicable as a guidance for further research in relation to the participation of religious groups.